Catalytic activation of nitrobenzene on PVP passivated silver cluster: A DFT investigation - Shukla M.; Sinha I. (My University, 2025)
Poly(N-vinyl-2-pyrrolidone) (PVP) has been used extensively to stabilize the surface of noble metal nanoparticles against aggregation and also to produce anisotropic nanostructures. Naturally, it is very important to understand the effect of such surface stabilization by PVP on the catalytic activity of these nanoparticles. This communication investigates through DFT calculations the electronic properties of PVP stabilized 13-atom Ag cluster for catalytic activation of nitrobenzene (NB). These computations suggest that poly(N-vinyl-2-pyrrolidone) (PVP) interact with silver (Ag) cluster mainly through oxygen atom and acts not only as a stabilizer to prevent the aggregation of Ag clusters but also as an electron donor to activate the Ag clusters for further reaction. Natural Bonding Orbital (NBO) calculations show that catalytic activation of NB by PVP passivated Ag cluster occurs due to interaction of the oxygen of the nitro group with the Ag cluster. Weak back donation of electrons from M(dπ) orbital of Ag to antibonding σ* of one of the NO bond, facilitates the formation of the nitroso intermediate. To understand the extent and the nature of this interaction better, vibrational frequency calculation of nitrobenzene association with Ag13-2PVP cluster is carried out. Red shift in the frequencies is consequence of strong interaction with that of silver cluster present in Ag13-2PVP-NB model. © 2017 Wiley Periodicals, Inc.